Nivolumab versus placebo in patients with relapsed malignant mesothelioma (CONFIRM): a multicentre, double-blind, randomised, phase 3 trial. Issue 11 (November 2021) - Fennell, Dean A; Ewings, Sean; Ottensmeier, Christian; Califano, Raffaele; Hanna, Gerard G; Hill, Kayleigh; Danson, Sarah; Steele, Nicola; Nye, Mavis; Johnson, Lucy; Lord, Joanne; Middleton, Calley; et al.
Summary: Background: No phase 3 trial has yet shown improved survival for patients with pleural or peritoneal malignant mesothelioma who have progressed following platinum-based chemotherapy. The aim of this study was to assess the efficacy and safety of nivolumab, an anti-PD-1 antibody, in these patients. Methods: This was a multicentre, placebo-controlled, double-blind, parallel group, randomised, phase 3 trial done in 24 hospitals in the UK. Adult patients (aged ≥18 years) with an Eastern Cooperative Oncology Group performance status of 0 or 1, with histologically confirmed pleural or peritoneal mesothelioma, who had received previous first-line platinum-based chemotherapy and had radiological evidence of disease progression, were randomly assigned (2:1) to receive nivolumab at a flat dose of 240 mg every 2 weeks over 30 min intravenously or placebo until disease progression or a maximum of 12 months. The randomisation sequence was generated within an interactive web response system (Alea); patients were stratified according to epithelioid versus non-epithelioid histology and were assigned in random block sizes of 3 and 6. Participants and treating clinicians were masked to group allocation. The co-primary endpoints were investigator-assessed progression-free survival and overall survival, analysed according to the treatment policy estimand (an equivalent of the intention-to-treat principle). All patients who were randomly assigned were included in the safety population, reported according to group allocation. This trial is registered with Clinicaltrials.gov, NCT03063450 . Findings: Between May 10, 2017, and March 30, 2020, 332 patients were recruited, of whom 221 (67%) were randomly assigned to the nivolumab group and 111 (33%) were assigned to the placebo group). Median follow-up was 11·6 months (IQR 7·2–16·8). Median progression-free survival was 3·0 months (95% CI 2·8–4·1) in the nivolumab group versus 1·8 months (1·4–2·6) in the placebo group (adjusted hazard ratio [HR] 0·67 [95% CI 0·53–0·85; p=0·0012). Median overall survival was 10·2 months (95% CI 8·5–12·1) in the nivolumab group versus 6·9 months (5·0–8·0) in the placebo group (adjusted HR 0·69 [95% CI 0·52–0·91]; p=0·0090). The most frequently reported grade 3 or worse treatment-related adverse events were diarrhoea (six [3%] of 221 in the nivolumab group vs two [2%] of 111 in the placebo group) and infusion-related reaction (six [3%] vs none). Serious adverse events occurred in 90 (41%) patients in the nivolumab group and 49 (44%) patients in the placebo group. There were no treatment-related deaths in either group. Interpretation: Nivolumab represents a treatment that might be beneficial to patients with malignant mesothelioma who have progressed on first-line therapy. Funding: Stand up to Cancer–Cancer Research UK and Bristol Myers Squibb.